2015
DOI: 10.1016/j.etp.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Topical nitrogen mustard exposure causes systemic toxic effects in mice

Abstract: Vesicating agents sulfur mustard (SM) and nitrogen mustard (NM) are reported to be easily absorbed by skin upon exposure causing severe cutaneous injury and blistering. Our studies show that topical exposure of NM (3.2 mg) onto SKH-1 hairless mouse skin, not only caused skin injury, but also led to significant body weight loss and 40–80 % mortality (120 h post-exposure), suggesting its systemic effects. Accordingly, further studies herein show that NM exposure initiated an increase in circulating white blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 78 publications
(109 reference statements)
2
19
0
Order By: Relevance
“…28,29 The previously published report has shown that cutaneous exposure of SM and its analogue not only limited to local injury but also caused a systemic effect. 30,31 The systemic effect occurs mainly due to the overexpression of inflammatory cytokines, which leads to organ dysfunction resulting in severe body weight loss 31,32 In the present study also, a severe decrease in body weight and morphological change were observed which suggest this could be results of intestinal epithelial damage which leads to insufficiency of dietary nutrients. Previously, Batal et al reported comparative internal organs toxicity after cutaneous exposure of SM and found that lung was the second most affected organ following cutaneous exposure of SM.…”
Section: Preventive Effect Of Amifostine and Drde-07 On Lung Inflammasupporting
confidence: 57%
“…28,29 The previously published report has shown that cutaneous exposure of SM and its analogue not only limited to local injury but also caused a systemic effect. 30,31 The systemic effect occurs mainly due to the overexpression of inflammatory cytokines, which leads to organ dysfunction resulting in severe body weight loss 31,32 In the present study also, a severe decrease in body weight and morphological change were observed which suggest this could be results of intestinal epithelial damage which leads to insufficiency of dietary nutrients. Previously, Batal et al reported comparative internal organs toxicity after cutaneous exposure of SM and found that lung was the second most affected organ following cutaneous exposure of SM.…”
Section: Preventive Effect Of Amifostine and Drde-07 On Lung Inflammasupporting
confidence: 57%
“…Without treatment, the lesion deepened and progressively worsened by day 10 post-exposure. The systemic toxic effects of NM reaches beyond local injury to cause cytopenia in blood, loss of intestinal barrier function, dilation of capillaries in the kidney, and bone marrow suppression 9,15 . Thus, the model is consistent with work previously reported by us and others that NM and SM induced skin vesication progressively deteriorates into a full thickness wound if continued inflammation is not suppressed by intervention with an anti-inflammatory drug 9,16 .…”
Section: Discussionmentioning
confidence: 99%
“…NM is particularly toxic to the skin, and able to cause systemic toxicity from topical absorption[22]. However unlike SM, NM has never been used in combat and fell out of favor for military use due to difficulties with its storage[23].…”
Section: 0 Overview Of the Evidence For Oxidative Stress In Cwas Anmentioning
confidence: 99%
“…NM may have a similar mechanism of action as SM due to its high reactivity, ability to alkylate DNA, and cause oxidative stress. NM mechanism of action produces DNA alkylation that is mediated with an immonium ion instead of a sulphonium ion[22]. NM is believed to directly cause oxidative stress in affected tissues, which then mediates activation of signaling pathways leading to cell microvesication and death[24].…”
Section: 0 Overview Of the Evidence For Oxidative Stress In Cwas Anmentioning
confidence: 99%